2018
DOI: 10.1155/2018/1460195
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Insertion Type and Depth on the Pedicle Screw Pullout Strength: A Finite Element Study

Abstract: Purpose The pedicle screw is a surgical device that has become widely used in spinal fixation and stabilization. Postsurgical complications such as screw loosening due to fatigue loading and screw breakage still need investigations. Clinical parameters such as the screw insertion type and depth, the bone density, and the patient degree of mobility greatly affect the mechanisms of the implant's failure/success. Methods The current finite element study focused on the prediction of the pedicle screw pullout stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 19 publications
2
13
1
Order By: Relevance
“…Patients inserted with 4 short screws gave lower VAS and ODI compared with others. This may show that radiographic difference in LS and SS and 4S and 6S may not affect with age [8]. Anchorage of pedicle screws strongly depend on their implantation depth and thus loosening the screw is easily done on partially embedded screws [6].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Patients inserted with 4 short screws gave lower VAS and ODI compared with others. This may show that radiographic difference in LS and SS and 4S and 6S may not affect with age [8]. Anchorage of pedicle screws strongly depend on their implantation depth and thus loosening the screw is easily done on partially embedded screws [6].…”
Section: Discussionmentioning
confidence: 97%
“…Several observed cases showed that the inserted screws had variable depths of penetration. Due to excessive mechanical stress, some of these screws had undergone failure in vivo [ 8 ]. To evaluate the effect of the inserted screw number and depth on spinal global balance, we analyzed the following key parameters: pelvic incidence (PI), pelvic tilt (PT), sacral slope (SS), and extent of spinal curvatures, especially lumbar lordosis (LL), segment lordosis (SL), and fractured vertebral lordosis (FL).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This force was defined for being close to the force of failure in a typical pullout strength test [10]. The von Mises stresses were evaluated in the cortical portion of the bone surrounding the screw [12,23].…”
Section: Methodsmentioning
confidence: 99%
“…The load at failure is influenced by several factors, including but not limited to the studied vertebra, bone density, insertion angle, insertion technique and screw geometry. The force at failure is usually in the 200 N to 800 N range [3,4,[9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%